Experimental evaluation of urinary bladder marsupialization in male lambs and calves - Canpolat, I; Bulut, S (Indian Veterinary Journal, 2005)
Urethral obstruction occurred up to 10% in male sheep (Hay, 1990) and 3-10% of male cattle (Hawkins 1965; Kimbeling and Arnold, 1983). Mortality rates in untreated cases may be 100% Hay (loc. cit.). Several surgical techniques to correct the urethral obstruction had been described such as local stone removal, urethrostomy, penile amputation, ischial urethrotomy, fistulation and catheterisation of bladder (Cockroft, 1993; Gasthuys et al., 1993; Haven et al,, 1993; Rakestraw et al., 1995). In a retrospective study, bladder marsupialization was evaluated as a primary procedure to study the long-term outcome when compared to other surgical procedures or when financial consideration dictated selection of a more economical procedure (May et al., 1998; May et al., 2002). The purpose of the study reported here was to provide a clinical evaluation of the effects of urinary bladder marsupialization in the male lamb and calf.
Keywords: Obstructive Urolithiasis; Small Ruminants; Male Goats